2006
DOI: 10.1189/jlb.0506356
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 deficiency causes altered inflammation with impaired skeletal muscle regeneration

Abstract: We examined the role of MCP-1, a potent chemotactic and activating factor for macrophages, in perfusion, inflammation, and skeletal muscle regeneration post-ischemic injury. MCP-1-/- or C57Bl/6J control mice [wild-type (WT)] underwent femoral artery excision (FAE). Muscles were collected for histology, assessment of tissue chemokines, and activity measurements of lactate dehydrogenase (LDH) and myeloperoxidase. In MCP-1-/- mice, restoration of perfusion was delayed, and LDH and fiber size, indicators of muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(181 citation statements)
references
References 61 publications
8
164
1
Order By: Relevance
“…3). It was reported that muscle regeneration was impaired in CCL2 Ϫ/Ϫ mice with less macrophage infiltration (8), which was consistent with our result that there was less CCL2 production in IL-6 Ϫ/Ϫ mice with less macrophage infiltration.…”
Section: Cd11bsupporting
confidence: 82%
See 1 more Smart Citation
“…3). It was reported that muscle regeneration was impaired in CCL2 Ϫ/Ϫ mice with less macrophage infiltration (8), which was consistent with our result that there was less CCL2 production in IL-6 Ϫ/Ϫ mice with less macrophage infiltration.…”
Section: Cd11bsupporting
confidence: 82%
“…Depletion of the macrophage population before cardiotoxin injection or after necrotic cell removal all lead to an impaired regeneration (6,7). Knock-out of chemokine CCL2 (Ϫ/Ϫ) or its receptor CCR2 (Ϫ/Ϫ) would result in impaired muscle regeneration with macrophages infiltration deficiency (8,9). We also previously reported that lack of chemokine CXCL16 leads to reduced macrophage infiltration, which causes poor muscle regeneration (10).…”
mentioning
confidence: 99%
“…The molecular pathways by which macrophages sustain muscle regeneration are still unclear (7,8,65). Notably, macrophages secrete both signals such as TNF-a that worsen muscle wasting via activation of the FOXO transcription factor (66, 67) and molecules that have an opposite function, such as IGF-1, a central regulator of muscle regeneration (7,56,57), or IL-10 (59, 68, 69).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the context, MPs may have supportive or deleterious eff ects on cells: in chronic diseases, including those aff ecting skeletal muscle, MPs are deleterious (62, 63), whereas they support tissue repair in muscle and other various tissues, including the liver, brain, peripheral nerve, and epithelium (19)(20)(21)(22)(64)(65)(66)(67). With the exception of regulation of infl ammation, studies documenting a direct role of MPs on cell behavior are scant and include intestinal progenitor proliferation (65), erythroblast proliferation and maturation (68), and oligodendrocytic diff erentiation and myelination (69).…”
Section: Articlementioning
confidence: 99%